MawuAP1 promotes flowering and fruit development in the basal angiosperm Magnolia wufengensis (Magnoliaceae). (27th April 2020) - Li, Cunjie; Chen, Liyuan; Fan, Xiaoning; Qi, Wenjuan; Ma, Jiang; Tian, Tian; Zhou, Tao; Ma, Luyi; Chen, Faju
Abstract: The APETALA1/SQUAMOSA (AP1/SQUA)-like genes of flowering plants play crucial roles in the development processes of floral meristems, sepals, petals and fruits. Although many of the AP1 / SQUA -like genes have been characterized in angiosperms, few have been identified in basal angiosperm taxa. Therefore, the functional evolution of the AP1 / SQUA subfamily is still unclear. We characterized an AP1 homolog, MawuAP1, from Magnolia wufengensis that is an ornamental woody plant belonging to the basal angiosperms . Gene sequence and phylogenetic analyses suggested that MawuAP1 was clustered with the FUL -like homologous genes of basal angiosperms and had FUL motif and paleoAP1 motif domain, but it did not have the euAP1 motif domain of core eudicots. Expression pattern analysis showed that MawuAP1 was highly expressed in vegetative and floral organs, particularly in the early stage of flower bud development and pre-anthesis. Protein–protein interaction pattern analysis revealed that MawuAP1 has interaction with an A-class gene ( MawuAP1 ), C-class gene ( MawuAG-1 ) and E-class gene ( MawuAGL9 ) of the MADS-box family genes. Ectopic expression in Arabidopsis thaliana indicated that MawuAP1 could significantly promote flowering and fruit development, but it could not restore the sepal and petal formation of ap1 mutants. These results demonstrated that there are functional differences in the specification of sepal and petal floral organs and development of fruits among the AP1 / SQUA- like genes, and functional conservation in the regulation of floral meristem. These findings provide strong evidence for the important functions of MawuAP1 in floral meristem determination, promoting flowering and fruit development, and further highlight the importance of AP1 / SQUA subfamily in biological evolution and diversity.